Presumed Ocular Tuberculosis: a Retrospective Case Review - Grodsky, Jacob D.; Lee, John; Piri, Niloofar (Journal of Ophthalmology and Research, 2022)
Despite the common misconception that tuberculosis (TB) is an uncommon disease in developed countries such as the United States; cases have become increasingly more prevalent. While 80% of patients diagnosed with TB have pulmonary findings, one common extrapulmonary presentation of TB is ocular involvement. In this retrospective case series, we present the clinical findings in nine cases of presumed ocular TB. All nine of these patients presented with an inflammatory component of their ocular TB manifestation. All patients who completed systemic TB treatment achieved quiescence of their ocular inflammation without flare up. Most of these patients had undiagnosed TB at their time of presentation, thus, highlighting the importance of further studies leading to more precise diagnostic guidelines and protocols. This will help ensure uniformity in care so that patients will be diagnosed and treated in a timely manner in order to prevent irreversible visual damage secondary to intraocular inflammation. Over the ten year time period included in this study, one-third of the patients were diagnosed over the past one year, suggesting potentially rising TB numbers in the US.